Integrasi Dan Penerapan Teori Signiant-Signified Saussure Dalam Pembelajaran Mufradāt - Nurmuzib, Moh Arif; Mubin, Khoirul; Setiyawan, Agung (STIQ Amuntai, 2024)
Learning Arabic mufradat, strategies, methods, and approaches are often less meaningful and only a formality for students. This research describes integrating Saussure's signifier-signified theory into Arabic vocabulary learning. The process in this research uses library research, which is a method of collecting data then understanding the data and studying theories from various sources of articles, and books by the research. The results of this study show that Saussure's signifiant-signified theory in the application of the principles of the relationship between the signifier and signified includes four aspects, including a) written sign (sign in the form of writing, b) oral-audio sign (sign in the form of sound), c) visual sign (sign in the form of pictures), d) object sign (a sign of a concrete object). Implementation in learning should be done sequentially, starting from the written sign as an introduction to the vocabulary and its meaning, oral-audio sign as an improvement of pronunciation, visual sign as strengthening mastery of mufradat, and object sign as contextual use of mufradat.